2021
DOI: 10.1177/1687814021996919
|View full text |Cite
|
Sign up to set email alerts
|

Phase difference and stability of a shaft mounted a dry friction damper: Effects of viscous internal damping and gyroscopic moment

Abstract: This study investigates the stability and phase difference of a shaft mounted a dry friction damper with effects of viscous internal damping and gyroscopic moment. The equations of the system with the vibration reduction effect of the dry friction damper on the shaft are derived in the form of the rectangular coordinate and polar coordinate in the vicinity of critical speed. The phase difference characteristics in the rub-impact process and its physical mechanism are analyzed by mathematical derivation. The ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…On the basis of the continuous model development for a slender shaft in Ref. [9,25], we have extended it to incorporate more than two shafts. This model relies on the Bernoulli-Euler beam theory [26], expressing its displacement through mode superposition.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…On the basis of the continuous model development for a slender shaft in Ref. [9,25], we have extended it to incorporate more than two shafts. This model relies on the Bernoulli-Euler beam theory [26], expressing its displacement through mode superposition.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Due to the fact that Ao > 0 and A3 > 0, the conditions (59) are reduced to The Hopf bifurcation boundary of the full annular solution is numerically solved. The boundary of Hopf bifurcation reveals the transition from synchronous full annular rub motion to partial rub motion [9,18].…”
Section: The Study Of Stabilitymentioning
confidence: 99%
“…The stability analysis and change in phase difference of the shaft and dry friction damper system having viscous internal damping and gyroscopic moment under coupling of unbalanced force and nonlinear rub-impact excitation was considered by Huang et al [18]. It was found that the viscous internal damping has a contribution to improving the stability of the synchronous full annular rub solution, the rub-impact delays the change in phase difference and the gyroscopic moment has an influence on the increase in the phase difference.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of damper parameters other than critical dry friction force was neglected, leading to the design of the damper cannot be further optimized. In their later study, the effects of viscous internal damping of the composite shaft and gyroscopic moment on the phase difference and stability regions of the shaft/damper system were presented (Huang et al, 2021b). However, the damper was regarded as static, resulting in that the shaft/damper system was equal to a typical rotor-stator system with immovable stator actually.…”
Section: Introductionmentioning
confidence: 99%